2013
DOI: 10.1037/a0033073
|View full text |Cite
|
Sign up to set email alerts
|

Assessing psychologists in practice: Lessons from the health professions using multisource feedback.

Abstract: The aim of the present study was to conduct a systematic literature review of multisource feedback (MSF) instruments and to summarize the evidence of feasibility, reliability, generalizability, validity, and other psychometric characteristics of the instruments. Accordingly, we conducted a systematic literature review for English-language studies published from 1975 to 2012 using the following databases: MEDLINE, EMBASE, CINAHL, PubMed, and PsycINFO. The following terms were used in the search: multisource fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 88 publications
1
27
0
Order By: Relevance
“…Obtaining appraisals from people in multiple roles increases the perceived value of feedback (Overeem et al 2010) and multiple observations give the feedback strength (Atwater et al 2002, Brinkman et al 2007, Castanelli & Kitto 2011. Despite the benefits, CNEs in this study experienced difficulty engaging raters, an issue that has been identified as a common barrier when implementing the MSF process (Andrews et al 2013).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Obtaining appraisals from people in multiple roles increases the perceived value of feedback (Overeem et al 2010) and multiple observations give the feedback strength (Atwater et al 2002, Brinkman et al 2007, Castanelli & Kitto 2011. Despite the benefits, CNEs in this study experienced difficulty engaging raters, an issue that has been identified as a common barrier when implementing the MSF process (Andrews et al 2013).…”
Section: Discussionmentioning
confidence: 87%
“…Despite the benefits, CNEs in this study experienced difficulty engaging raters, an issue that has been identified as a common barrier when implementing the MSF process (Andrews et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…We discussed the needs, challenges, and available methods for assessment with stakeholders (such as students, assessors, and supervisors). In addition, we conducted a study of literature on competency assessment in sport psychology (e.g., Fletcher & Maher, 2013Tashman, 2010), professional psychology (e.g., Fouad et al, 2009;Gonsalvez et al, 2013;Kaslow et al, 2009;Muse & McManus, 2013;Newell, Newell, & Looser, 2013;Petti, 2008;Schulte & Daly, 2009;Yap, Bearman, Thomas, & Hay, 2012), and medicine (e.g., Andrews, Violato, Ansari, Donnon, & Pugliese, 2013;Dijkstra, van der Vleuten, & Schuwirth, 2009;Epstein, 2007;McMullan et al, 2003;Schuwirth & van der Vleuten, 2011).…”
Section: Planning Actionmentioning
confidence: 99%
“…The wide adoption of MSF across a multitude of medical disciplines internationally predicates an inherent need to critically evaluate evidence to support or refute its validity. Whilst a number of systematic reviews demonstrate MSF to be a valid, reliable and feasible method of performance assessment [8][9][10][11] , critics regularly cite concerns around important issues that may undermine assessment validity [12][13][14] . Past reviews have largely focussed on specific areas of assessment validity (e.g.…”
Section: Introductionmentioning
confidence: 99%